2022
DOI: 10.1021/acschembio.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Activation of the Cryptic Cluster from Aspergillus sp. CPCC 400735 for Asperphenalenone Biosynthesis

Abstract: Postgenomic analysis manifested that filamentous fungi contain numerous natural product biosynthetic gene clusters in their genome, yet most clusters remain cryptic or down-regulated. Herein, we report the successful manipulation of strain Aspergillus sp. CPCC 400735 that enables its genetic engineering via targeted overexpression of pathway-specific transcriptional regulator AspE. The down-regulated metabolic pathway encoded by the biosynthetic gene cluster asp was successfully up-activated. Analyses of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Genomic DNA from Desarmillaria was isolated using HP Fungal DNA Kit (Omega, Guangzhou, China) according to the manufacturer's instructions. Further purification was conducted using RNase digestion, chloroform extraction, and isopropanol precipitation [29]. The high molecular weight gDNA was washed twice with 75% ethanol, and dissolved in 200 µL RNase-free water.…”
Section: Strains and Cultivation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA from Desarmillaria was isolated using HP Fungal DNA Kit (Omega, Guangzhou, China) according to the manufacturer's instructions. Further purification was conducted using RNase digestion, chloroform extraction, and isopropanol precipitation [29]. The high molecular weight gDNA was washed twice with 75% ethanol, and dissolved in 200 µL RNase-free water.…”
Section: Strains and Cultivation Conditionsmentioning
confidence: 99%
“…The oligonucleotide primers used for constructing the genes are listed in Table 1. PCR reactions were performed using Q5 High-Fidelity DNA Polymerase (New England Biolabs) according to the manufacturer's protocol at an annealing temperature of 56 • C. In vivo yeast recombination cloning strategy was performed using a Frozen-EZ Yeast Transformation II Kit™ (Zymo Research) where competent cell S. cerevisiae BJ5464 was transformed with the individual DNA fragment (PCR product) of the respective STS gene and linearized vector backbone derived from YET plasmid [28,29]. Yeast transformants grown on synthetic dropout agar plate lacking tryptophan were screened by diagnostic PCR.…”
Section: Gene Synthesis Cloning and Expression Of Stss In Yeastmentioning
confidence: 99%
“…Meanwhile, we could now easily access to the sequenced genome of targeted microorganism whose metabolites have not been, or rarely, characterized. Genome-guided mining approach is usually conducted to set up the linking between secondary metabolites identification and targeted biosynthetic gene clusters (BGCs) verification [ 11 , 12 ]. Also, previous studies have demonstrated that genome mining is an effective approach that facilitated exploitation for new metabolites with fascinating structures, and numerous BGCs were investigated [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%